Factors associated with subclinical atherosclerosis in HIV infected patients from northeast of Brazil (Research, Society and Development, 2021)
Introduction: AIDS has changed its morbidity curve, rising cardiovascular diseases. HIV-infected patients have increased cardiovascular event rates but data on the prevalence of subclinical atherosclerosis are not uniform. Methods: HIV-infected patients underwent to coronary tomography for CACs assessement. We performed a comparison between 97 HIV-infected patients and 129 seronegative healthy controls. The univariable analysis matched the association of HIV infection, cardiovascular risk profile, and HIV-related factors with subclinical atherosclerosis. Results: HIV-infected patients with CACs above zero were older (54.8±7.0 vs. 43.3.5±11.0 years; p